2014
DOI: 10.1158/1078-0432.ccr-13-3224
|View full text |Cite
|
Sign up to set email alerts
|

miR-141 Is a Key Regulator of Renal Cell Carcinoma Proliferation and Metastasis by Controlling EphA2 Expression

Abstract: Purpose: Although microRNAs (miRNA) have been revealed as crucial modulators of tumorigenesis, our understanding of their roles in renal cell carcinoma (RCC) is limited. Here we sought to identify human miRNAs that act as key regulators of renal carcinogenesis.Experimental Design: We performed microarray-based miRNA profiling of clear cell RCC (ccRCC) and adjacent normal tissues and then explored the roles of miR-141 both in vitro and in vivo, which was the most significantly downregulated in ccRCC tissues.Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 50 publications
3
117
0
3
Order By: Relevance
“…We concluded that miR-200s family should be important regulators during development of RCC. Our published data of miR-141 have revealed that main function of miR-141 is to inhibit invasion and metastasis by controlling EphA2 expression in RCC (31). Here, for the first time, we demonstrated that miR-200c could suppress cell growth and tumorigenesis both in vitro and in vivo by directly targeting CDK2.…”
Section: Discussionmentioning
confidence: 64%
“…We concluded that miR-200s family should be important regulators during development of RCC. Our published data of miR-141 have revealed that main function of miR-141 is to inhibit invasion and metastasis by controlling EphA2 expression in RCC (31). Here, for the first time, we demonstrated that miR-200c could suppress cell growth and tumorigenesis both in vitro and in vivo by directly targeting CDK2.…”
Section: Discussionmentioning
confidence: 64%
“…(A humán vesekarcinómában és sejtvonalakban leggyakrabban elő-forduló up-és downregulált miR-eket az 1-2. táblázat foglalja össze). Egy másik tanulmány szerint, a miR-34, -21, valamint a -224 overexpressziót mutatott, a miR-141 pedig downregulált volt az Rcc-s betegek szérumában (9,15,16). A vesetumoros betegek szérumában a miR-21, miR-221 és a miR-222 viszont emelkedett volt az egészséges kontrollhoz képest (9,11,12,15).…”
Section: A Vesetumorokban Leggyakrabban Előforduló Mir-ekunclassified
“…A ccRcc normálvesétől tör-ténő elkülönítésében lehetséges biomarkerként említhető a miR-141, amely egyidejűleg jelentős tumorszuppresszor szerepet tölthet be a ccRcc fejlődésében és a metasztázis szabá-lyozásában is (9,16). A miR-141 és a miR-155 expressziója eddig a vizsgált veseminták 97%-ánál tette lehetővé a pontos klasszifikációt (9,17).…”
Section: Táblázat: a Humán Vesekarcinómában éS Sejtvonalakban Leggyakunclassified
See 1 more Smart Citation
“…MiRNAs can regulate gene expression through directly binding to 3' UTR of mRNA or coding sequence [1,2]. They are involved in various physiological and pathological processes such as cell differentiation, proliferation and apoptosis [3,4]. Dysregulation of miRNAs are related with cancers [5], atherosclerosis [6] and other diseases.…”
Section: Introductionmentioning
confidence: 99%